Explanatory model of academic self-efficacy: self-regulation of activities, positive affection, and personality - Yupanqui-Lorenzo, Daniel Edgardo (2021)
Academic self-efficacy is a powerful predictor of academic success, yet there are several factors that predispose it. Because of this, an explanatory model is proposed using the self-regulation of academic activities, positive affection, and personality. Hierarchical multiple linear regression was used to support the predictive proposal of the model. The Specific Perceived Self-Efficacy Scale of Academic Situations, The Scale of Positive and Negative Experience, Subscale Self-Regulation of Activities of the Academic Procrastination Scale, and Mini International Personality Item Pool (MINI-IPIP) were used. High correlations were obtained in the self-regulation of activities, positive affection, and personality (extraversion, concientousness and openness to experience) to academic self-efficacy. The final predictive model explained 30.1% of the total variance of academic self-efficacy. In conclusion, the model proposed through literature review is a strong predictor of academic self-efficacy and promotes the development of self-effective beliefs.